(untitled) (Journal of the College of Basic Education, 2025)
The research aims to examine the relationship between the level of life skills and creative thinking among pre-university chemistry students in Baghdad Governorate.The researcher relied on the descriptive-analytical approach to achieve his goal, as the descriptive-analytical approach is considered the appropriate method for describing the phenomenon under study, arriving at and analyzing results, and providing recommendations. A random sample of 100 individuals from the study population was selected. A questionnaire was used as the research tool.The study concluded that life skills education has a positive and statistically significant impact on creative thinking in the sample studied.In light of the findings, the researcher developed a set of recommendations and proposals for future research.